The effects of source characteristics, psychological-related influential factors, and content attributes on purchase intentions: A case study on BLK Cosmetics Philippines - Alonte, Alexis Therese L. (Animo Repository, 2022)
BLK Cosmetics Philippines is a cosmetics company that provides affordable high-quality products to the Philippine market. BLK has integrated influencer marketing to better connect with its customers. Influencer Marketing is a widely used strategy where social media influencers are in agreement with businesses to create awareness about their brand. This study determined the relationship between the three aspects of influencers: Source Characteristics (Attractiveness & Popularity), Psychological-Related Influential Factors (Self-Congruency & product Match-up), and Content Attributes (Quality & Uniqueness) with BLK’s Customer Purchase Intention. This is the first research attempt to relate all six of these variables to Customer Purchase Intention. The study utilized a causal research design to achieve the objectives of the study. Through random sampling, the study’s sample size of 387 was garnered from the Instagram followers of BLK. An online questionnaire distributed via Instagram consisted of statements regarding the variables wherein the respondents expressed their agreement or disagreement using a seven-point Likert scale. Using Multiple Linear Regression, the study’s results revealed that Attractiveness, Uniqueness, and Self-Congruency were the only variables that proved to be significant. With Attractiveness having the highest effect on Customer Purchase Intention, followed by Uniqueness then Self-Congruency.